Dysregulation of Autophagy, Mitophagy, and Apoptosis Genes in the CA3 Region of the Hippocampus in the Ischemic Model of Alzheimer’s Disease in the Rat - Ułamek-Kozioł, Marzena (J Alzheimers Dis, 2019)
There is currently no knowledge about the expression profile of the autophagy (BECN1), mitophagy (BNIP3), and apoptosis (CASP3) genes in the CA3 region of the hippocampus after cerebral ischemia. In addition, it is unknown whether genes for BECN1, BNIP3, and CASP3 have any effect on the neuronal death in the CA3 area of the hippocampus due to ischemia. In this study, for the first time, we present, by means of a quantitative PCR protocol with reverse transcriptase, the expression of BECN1 and CASP3 genes in the neuronal CA3 region of the hippocampus with the co-expression of the mitochondrial BNIP3 gene, which genes are associated with Alzheimer’s disease, in the ischemic model of Alzheimer’s disease in the rat. The present study showed that after ischemia, the CASP3 gene was significantly expressed within 7–30 days, the BECN1 gene was significantly overexpressed on the thirtieth day, and the BINP3 gene was lowered below control values during post-ischemic follow-up period. The caspase-dependent neuronal death in the CA3 region of the hippocampus after ischemia is not accompanied by overexpression of the BNIP3 gene. Our data may therefore suggest a new insight into the BNIP3 gene in the regulation of neuronal mitophagy in neurodegeneration in the CA3 region of the hippocampus after ischemia. This indicates no involvement of the BNIP3 gene along with the CASP3 gene in the CA3 region of the hippocampus in delayed neuronal death after brain ischemia.